PENERAPAN MODEL DIRECT INSTRUCTION UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATERI KALOR DAN PERPINDAHANNYA - Kristiana Renny; Haratua Tiur Maria Silitonga; Hamdani Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis study aims to improve students learning outcomes, through the application of the Direct Instruction model to the heat and displacement material. The design of this study was in the form of One-Group Pretest-Posttest Design which involved 32 students at SMPN 1 Sungai Raya. Data collection includes tests of students learning outcomes in the form of pretest and posttest consisting of 5 multiple choice questions and 3 essay questions. The average achievement results were 30.62 and 79.68 posttest. Wilcoxon test results show that there are significant differences in students learning outcomes before and after the implementation of the Direct Instruction model in the teaching and learning process and the effect size of this research model is 4.60 with a high category, it can be concluded that the application of the Direct Instruction model can improve students learning outcomes students on the heat and displacement material. Suggestions, that the Direct Instruction learning model requires a longer time for certain materials, therefore it is recommended for future researchers that before applying the Direct Instruction learning model to other materials, first set the time so that the material to be delivered can be given according to the time limit available.Keywords: Direct Instruction, Heat and displacement, Learning outcomes.